Efficacy of Topical Tretinoin, Benzoyl Peroxide and Oral Tetracycline Combination in Acne Vulgaris (TAJ: Journal of Teachers Association, 2009)
This study was done in the outpatient department of Rajshahi Medical College Hospital from January 2004 to December 2005. In this study the efficacy of topical tretinoin, benzoyl peroxide and oral tetracycline was studied in 50 patients. Forty five patients completed the course of treatment and 5 patients were defaulter. Complete remission was seen in 32 (71.11%), marked improvement in 08 (17.78%) and good response in 05 (11.11%) patients. Application of topical tretinoin cream (0.05%) in the evening, benzoyl peroxide cream (5%) in the morning and oral tetracycline (500 mg bd) before meal was found very effective, safe and cheap in the treatment of comedonal, pustular and pustulo-nodular acne vulgaris.   doi: 10.3329/taj.v19i1.3161 TAJ 2006; 19(1): 10-12